Solution and solid state (CPMAS) NMR studies of the tautomerism of six-membered heterocyclic compounds related to 2-pyridones. Issue 3 (2000) - López López, Concepción Concepción; Claramunt Claramunt, Rosa María Rosa María; Alkorta Alkorta, Ibon Ibon; Elguero Elguero, José José
Abstract : Several 13 C and 15 N chemical shifts of 2-pyridone(1), 4(3 H )-pyrimidone(2), uracil(3) and cytosine(4) have been measured in solution and in the solid state. These data have been discussed in relation with the tautomerism of the four heterocycles. GIAO ab initio calculations of absolute shieldings have been carried out to identify the predominant tautomers in the case of compounds(1) and(2) .